Speech activity among the junior students in teaching foreign languages - Abilgaziyeva, Zh. K.; Janzakova, Sh. I.; Nurgaliyeva, S.A. (Opción, 2019)
The article is devoted to the formation of speech activity among junior school students in the process of teaching foreign languages with the help of integrative learning technology through a personality-active method as the methodological basis of the integrative method. As a result, the technology of teaching foreign languages among the junior school students on an integrative basis reflects the mutual conditioning of the communicative and speech process development by the means of native and foreign language. As a conclusion, the given analysis showed inconsistency in Russian and English languages education.